The insulin-like growth factor-1 receptor is a negative regulator of nitric oxide bioavailability and insulin sensitivity in the endothelium - Abbas, A; Imrie, H; Viswambharan, H; Sukumar, P; Rajwani, A; Cubbon, R; Gage, M; Smith, J; Galloway, S; Yuldeshava, N; Kahn, M; Xuan, S; et al. (2011)
OBJECTIVE - In mice, haploinsufficiency of the IGF-1 receptor (IGF-1R +/2), at a whole-body level, increases resistance to inflammation and oxidative stress, but the underlying mechanisms are unclear. We hypothesized that by forming insulin-resistant heterodimers composed of one IGF-1Rαβ and one insulin receptor (IR), IRαβ complex in endothelial cells (ECs), IGF-1R reduces free IR, which reduces EC insulin sensitivity and generation of the antioxidant/anti-inflammatory signaling radical nitric oxide (NO). RESEARCH DESIGN AND METHODS - Using a number of complementary gene-modified mice with reduced IGF-1R at a whole-body level and specifically in EC, and complementary studies in EC in vitro, we examined the effect of changing IGF-1R/IR stoichiometry on EC insulin sensitivity and NO bioavailability. RESULTS - IGF-1R+/2 mice had enhanced insulin-mediated glucose lowering. Aortas from these mice were hypocontractile to phenylephrine (PE) and had increased basal NO generation and augmented insulin-mediated NO release from EC. To dissect EC from whole-body effects we generated mice with EC-specific knockdown of IGF-1R. Aortas from these mice were also hypocontractile to PE and had increased basal NO generation. Whole-body and EC deletion of IGF-1R reduced hybrid receptor formation. By reducing IGF-1R in IR-haploinsufficient mice we reduced hybrid formation, restored insulin-mediated vasorelaxation in aorta, and insulin stimulated NO release in EC. Complementary studies in human umbilical vein EC in which IGF-1R was reduced using siRNA confirmed that reducing IGF-1R has favorable effects on NO bioavailability and EC insulin sensitivity. CONCLUSIONS - These data demonstrate that IGF-1R is a critical negative regulator of insulin sensitivity and NO bioavailability in the endothelium. © 2011 by the American Diabetes Association.